ReWIND: A CBT-Based Serious Game to Improve Cognitive Emotion Regulation and Anxiety Disorder - Yew Ken Heng; Jasy Suet Yan Liew; Mohammad Farris Iman Leong Abdullah; Ying Tang; Nathan Prestopnik (Serious Games Society, 2023)
Games have shown successful intervention outcomes and can be used to complement the treatment of anxiety disorders. However, current serious game solutions are designed to be task-based rather than story-based. We present ReWIND, a serious role-playing game (RPG) applying cognitive behavioral therapy (CBT) to design anxiety-relevant storylines and game mechanics. ReWIND advances state-of-the-art mental health games by seamlessly integrating CBT elements and strategies into the game's storytelling so players can learn how CBT is applied in anxiety scenarios as they play through the game. Our goal is to examine the effectiveness of ReWIND in improving cognitive emotion regulation and anxiety disorders. Through a randomized controlled trial, 40 participants were recruited, of whom half were randomly assigned to play ReWIND while the others worked on a non-game task. Anxiety and cognitive emotion regulation levels were measured before and after the interventions. Our findings show ReWIND significantly reduces the severity level of anxiety symptoms and trait anxiety levels and increases perceived control of anxiety better than the non-game task. ReWIND also obtained positive ratings for its usability and practicality in real life, helping participants to cope better with anxiety disorders.